(untitled) (Journal of Plant Disease Sciences, 2021)
In present investigation total fifteen soil samples were collected from fifteen different locations of Maharashtra from diverse crop ecosystem and Azotobacter chroococcum was isolated. Physiological test was performed at different temperature and pH levels. All the isolates showed excellent growth at 30 p C and 35 p C temperature and showed good growth at pH 7.0. The test of tolerance with seed dresser fungicides at recommended field dosages 50%, 75%, 100% and 125% of the recommended doses were evaluated in vitro against A. chroococcum by inhibition zone technique. Among seed dresser carbendazim and mancozeb at all four concentrations were found compatible with A. chroococcum, as no zone of inhibition was observed at 72 hrs of incubation.